Endovascular Treatment of Acute Ischemic Stroke in Patients Younger than 18 Years - Dalai, Sibasankar; Limaye, Uday; Kolli, Satyarao; Maturu, Mohan V. Sumedha; Narayana, Randhi Venkata; Pati, Rajesh; Korada, Suresh Kumar; Vankineni, Kuchelababu; Sameera, Anantamakula; Datla, Aravind Varma (Journal of Clinical Interventional Radiology ISVIR, 2021)
Purpose Rapid and effective revascularization is very important in the treatment of acute ischemic stroke (AIS). Endovascular treatment is a promising modality in the management of AIS in young patients.Methods We evaluated the clinical and imaging records in 14 patients younger than 18 years presenting within 6 hours of AIS. They received endovascular therapy (ET) either by mechanical thrombectomy, thromboaspiration, or both (Solumbra) between July 2017 and June 2021. The National Institute of Health Stroke Scale (NIHSS) score was calculated on admission and before the discharge of all patients. The 90-day modified Rankin Scale (mRS) score on disability-free outcome was also evaluated.Results The mean preprocedure NIHSS score was 10.78 ± 2.11 that improved to 4.5 ± 1.88 after the procedure. Thrombolysis in cerebral infarction (TICI) grade 2b and 3 blood flow could be established in 12 (85.72%) patients. One patient had TICI 2a flow and one patient had recurrent occlusion despite repeated recanalization (TICI grade 0). The disability-free outcome, mRS score at 90 days was 0 to 1 in 12 (85.72%) patients, mRS score 2 in one (7.14%) patient, and mRS score 3 in one patient (7.14%). We did not have any major complication related to the procedure.Conclusion ET provides high rates of arterial recanalization and favorable disability-free outcomes in young patients with AIS.
Keywords: stroke in young; mechanical thrombectomy; thromboaspiration